ILMU MUNASABAH SEBAGAI ALTERNATIF ILMU ASBAB NUZUL AYAT AL-QUR’AN - Surya, Ilham; Wahyuni, Sri (Ma'had Aly As'adiyah Sengkang, 2024)
The purpose of this study is to describe the concept of munasabah as an alternative to the concept of asabab nuzul. This study uses a qualitative method of literature review. The analysis technique used is descriptive analysis technique. This research collects data from various literatures related to the study of munasabah in the Qur'an. The result of this study shows that munasabah is the right alternative to asbabun nuzul. The study of munasabah plays a significant role in explaining the context of a verse as well as the function of asbabun nuzul.